Targeting Exosomal PD-L1 as a New Frontier in Cancer Immunotherapy - Laura Denisa Dragu; Mihaela Chivu-Economescu; Ioana Madalina Pitica; Lilia Matei; Coralia Bleotu; Carmen Cristina Diaconu; Laura Georgiana Necula (Current Issues in Molecular Biology, 2025)
This manuscript assesses the critical role of exosomal PD-L1 (ExoPD-L1) in immune suppression, tumor progression, and resistance to therapy. ExoPD-L1 has been identified as a key mediator of tumor immune evasion, contributing to systemic immunosuppression beyond the tumor microenvironment (TME) due to its capacity to travel to distant anatomical sites. In this context, the review aims to elaborate on the mechanisms by which exosomal PD-L1 interacts with T cell receptors and modulates both the tumor microenvironment and immune responses, impacting patient outcomes. We further explore emerging therapeutic strategies that target ExoPD-L1 to enhance the effectiveness of immunotherapy. Blocking ExoPD-L1 offers a novel approach to counteracting immune escape in cancer. Promising strategies include inhibiting exosome biogenesis with GW4869 or Rab inhibitors, neutralizing ExoPD-L1 with targeted antibodies, and silencing PD-L1 expression through RNA interference (RNAi) or CRISPR-based methods. While each approach presents certain limitations, their integration into combination therapies holds significant potential to improve the efficacy of immune checkpoint inhibitors. Future research should focus on optimizing these strategies for clinical application, with particular attention to improving delivery specificity and minimizing off-target effects.